Distribusi Penyakit Demam Berdarah Dengue Berdasarkan Variabel Epidemiologi Di Kabupaten Ende - Tokan, Pius Kopong; Ahmad, Hamsir (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2024)
Dengue Dengue Fever (DBD) is a public health problem in the world, has an impact on economic loss and continues to be a burden on the country. Events that continue to increase and expand in the last five years are the basis for further studies. The purpose of the research is to determine the distribution of dengue fever based on Epidemiological Variables in Ende Regency in 2018-2022. Research method: using secondary data is descriptive research to assess the spread of dengue cases based on the epidemiological variables of people, places, and times. The subject of the study was the number of dengue cases in 2018-2022 as many as 609 cases. Data collection using secondary data observation techniques. Data processing starts with editing, tabulating, serving, and data presentation.Furthermore, it is analyzed in the form of frequency distribution and presented in the form of tables and graphs. Researchers emphasize the existence of research ethics, namely anonymity and confidentiality. Result: Dengue fever cases in Ende Regency in 2018-2022 attacked more men, namely 318 people (52.2%) and 219 women (47.8%); based on the distribution of wilayah, the most cases were in urban areas, the highest in ende City, then Onekore, Rukun lima, and Kota ratu. The surge in cases occurred in 2019 and 2020 due to the condition of the Covid 19 pandemic which has similarities in symptoms with dengue fever. Still, it decreased in 2021 and increased again in 2022, higher than the previous 5 years. Advice: more aimed at the Ende Regency Government to carry out various interventions by involving cross-sector roles and the active participation of the community in efforts to prevent and control dengue fever